Late Pliocene Gilbert Type Delta and Early Pleistocene Drainage System Changes in the Erzurum Basin, NE Turkiye - Celik, H.; Trifonov, V. G.; Tesakov, A. S.; Sokolov, S. A.; Frolov, P. D.; Simakova, A. N.; Bachmanov, D. M. (Pleiades Publishing Ltd, 2023)
The Late Pliocene Gilbert-type delta is described in the western Erzurum Basin (NE Turkiye) and its position in the Late Cenozoic development of the basin is defined. The Erzurum Basin originated no later than Late Miocene between two Mesozoic ophiolite zones, continuing the Izmir-Ankara-Erzincan suture. In the Late Miocene-Pliocene, the basin was filled with fine-grained clastic and carbonate sediments of lacustrine-lagoon type. The Gilbert-type delta formed at the top of these deposits in the western part of the basin. The delta consists of 11 wedge-shaped bodies of clay, silt, sand, and gravel that were deposited as foresets of different phases of the delta development. The foreset bodies are dipping at 5 degrees to 35 degrees E. Some bodies underwent soft sediment deformation. The delta deposits are dated to Late Pliocene based on remains of small mammals and molluscs, palynological, and magneto-stratigraphic analysis. The delta eroded surface is overlain by alluvial pebbles dated to Early Pleistocene by archaeological finds. The Erzurum Basin is the westernmost member in a row of intermontane basins that continues to the east with the Pasinler, Horasan, and Agri basins that are drained by the Araxes River and its tributaries. It is likely that the paleo-Araxes River spread to the west in Late Pliocene and the studied delta was formed by its upper reaches that flowed into the water body of the Erzurum Basin. The delta deposits were covered by coarse alluvium in Early Pleistocene when the Erzurum Basin was tectonically isolated from the Araxes drainage system. In the latest Early Pleistocene or early Middle Pleistocene, the paleo-Araxes upper reaches were captured by the Euphrates River upper reaches that drain the Erzurum Basin now. The Upper Miocene and Pliocene deposits of the Erzurum, Pasinler, and Horasan Basins are similar and were accumulated in a single basin of sedimentation. Therefore, it can be assumed that the deposits of the upper Pliocene, containing the Akchagylian marine biota in the Horasan Basin, extended into the Erzurum Basin. However, the assumption that the upper reaches of the Euphrates River and the Erzurum Basin were the channel, through which the open sea biota entered the Akchagylian basin, is very unlikely for two reasons. Firstly, the Erzurum basin was limited by the described delta of the river, which flowed into it from the west. Secondly, the upper reaches of the Euphrates penetrated into the Erzurum Basin after the completion of the Akchagylian stage of sedimentation.
Keywords: Erzurum Basin; Gilbert type delta; small mammals; molluscs; palynology; magneto-stratigraphy; Acheulian; Late Pliocene; Pleistocene; river capture